Degradacao termica e catalitica da borra oleosa de Petroleo com materiais nanoestruturados al-mcm-41 e AL-SBA-15 - Paulino, Ana Adalgisa Dias (2012)
Aiming to reduce and reuse waste oil from oily sludge generated in large volumes by the oil industry, types of nanostructured materials Al-MCM-41 and Al-SBA-15, with ratios of Si / Al = 50, were synthesized , and calcined solids used as catalysts in the degradation of oily sludge thermocatalytic oil from oilfield Canto do Amaro, in the state of Rio Grande do Norte. Samples of nanostructured materials were characterized by thermogravimetric analysis (TG / DTG), X-ray diffraction (XRD), scanning electron microscopy (SEM), absorption spectroscopy in the infrared Fourier transform (FT-IR) and adsorption nitrogen (BET). The characterization showed that the synthesized materials resulted in a catalyst nanostructure, and ordered pore diameter and surface area according to existing literature. The oily sludge sample was characterized by determining the API gravity and sulfur content and SARA analysis (saturates, aromatics, resins and asphaltenes). The results showed a material equivalent to the average oil with API gravity of 26.1, a low sulfur content and considerable amount of resins and asphaltenes, presented above in the literature. The thermal and catalytic degradation of the oily sludge oil was performed from room temperature to 870 ° C in the ratios of heating of 5, 10 and 20 ° C min-1. The curves generated by TG / DTG showed a more accelerated degradation of oily sludge when it introduced the nanostructured materials. These results were confirmed by activation energy calculated by the method of Flynn-Wall, in the presence of catalysts reduced energy, in particular in the range of cracking, showing the process efficiency, mainly for extraction of lightweight materials of composition of oily sludge, such as diesel and gasoline